Preparation method of magnetic control microcapsule for insulating medium electrical tree damage self-repairing
By synthetic magnetic control characteristics γ-Al2O3@SiO2 nanometer particles and magnetic control microcapsules, the magnetic field guides the micro-capsule to migrate, solving the difficulty of composite medium between high self-repair performance and low self-repair group division of doping quantity. The problem has achieved efficient self -cultivation effects.
Patent Information
- Application Number
- CN202310912572.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
AI Technical Summary
A problem that composite media is difficult to take into account between high self-repair performance and low self-repair component doping.
By synthesizing amphiphilic γ-Al2O3@SiO2 nanoparticles and using them to emulsify the core material of UV-sensitive repair liquid, magnetically controlled microcapsules were finally synthesized. This method uses a magnetic field to guide the directional migration of microcapsules to achieve efficient self-healing at low capsule doping levels.
The efficient self -repair of composite materials is achieved under the amount of low capsules, the repair effect is significant, and the breakdown intensity after repair remains above 95%of the epoxy resin substrate.
Smart Images

Figure CN119346013A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of repairing electrical tree damage of insulating medium of dry-type transformer, and in particular relates to a method for preparing magnetically controlled microcapsules for self-repairing electrical tree damage of insulating medium. Background Art
[0002] Dry-type transformers have been widely used in distribution networks due to their small size, easy layout, environmental protection, and good fire resistance. However, dry-type transformers will inevitably bear complex electrical, thermal, and mechanical stresses during operation, resulting in local defects, which in turn cause equipment insulation degradation or even failure.
[0003] When a dry-type transformer fails, the molecular chain segments of the epoxy resin insulation medium will gradually degrade, causing the partial discharge damage channel to extend radially (in the direction of the electric field) and axially (perpendicular to the electric field). The dendritic channel formed shortens the effective insulation distance and eventually leads to insulation failure. Therefore, it is very important to study the corresponding suppression measures.
[0004] At present, domestic and foreign scholars mainly introduce nanoparticles into the dielectric substrate through physical blending or chemical deposition, which can achieve the dual inhibition of the initiation and growth of electrical dendrites by nanocomposite dielectrics. Since the concept of dielectric self-repair was proposed at the beginning of this century, the research field of self-repairing composite dielectrics has made great progress. However, there is no technical solution to the problem of high self-repairing performance of composite dielectrics and low doping amount of self-repairing components. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in dry-type transformer insulating media, so as to solve the contradiction between high self-repair performance of composite media and low doping amount of self-repair components. The method synthesizes amphiphilic γ-Al2O3@SiO2 nanoparticles, uses them to emulsify ultraviolet photosensitivity repair liquid core materials, and finally synthesizes magnetically controlled microcapsules.
[0006] To achieve the above object, the present invention provides a method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in an insulating medium, comprising the following steps:
[0007] (1) acidifying the γ-Al2O3 nanoparticles, and then adding the acidified γ-Al2O3 nanoparticles to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water for ultrasonic treatment to obtain a γ-Al2O3 nanoparticle modified mixed solution;
[0008] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles to fully react, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles;
[0009] (3) washing the γ-Al2O3@SiO2 nanoparticles, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of anhydrous ethanol and deionized water to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0010] (4) adding a coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully, washing the product, and vacuum drying to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0011] (5) adding the microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion;
[0012] (6) mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath, and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution;
[0013] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; a curing agent and a pH regulator are continuously added to the Pickering emulsion, and the reaction is carried out in a water bath. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0014] Furthermore, in the step (1), the acid treatment liquid used for the acid treatment of the γ-Al2O3 nanoparticles is composed of sulfuric acid and hydrogen peroxide, and the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment liquid is: sulfuric acid: hydrogen peroxide = (6.5-7.5):3; the acid treatment temperature is 75-85°C, and the acid treatment time is 50-70 minutes; each liter of the acid treatment liquid can treat 4-6 grams of the γ-Al2O3 nanoparticles.
[0015] Furthermore, in the mixed solution of anhydrous ethanol, deionized water and concentrated ammonia water in the step (1), the volume ratio of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100: (23-27): (1.8-2.2); the concentrated ammonia water is an aqueous solution containing 25%-28% ammonia; and the ultrasonic treatment time is 50-70 minutes.
[0016] Furthermore, in the step (2), tetraethyl orthosilicate is added to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treated for 25 to 35 minutes, and the product is magnetically separated to obtain γ-Al2O3@SiO2 nanoparticles; wherein the amount of tetraethyl orthosilicate added per gram of the γ-Al2O3 nanoparticles in step (1) is 2.8 to 3.2 milliliters.
[0017] Furthermore, in the step (3), the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol:deionized water=(5-8):10.
[0018] Furthermore, the coupling agent in step (4) is a silane coupling agent, and the reaction temperature is between 68 and 72° C., wherein the amount of the silane coupling agent added is 80% to 150% of the weight of the γ-Al2O3 nanoparticles in step (1).
[0019] Furthermore, the microcapsule core material in step (5) is composed of epoxy resin, reactive diluent, photoinitiator and infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100: (8-12): (4-6): (0.08-0.12); the addition amount of the microcapsule core material corresponding to each gram of γ-Al2O3 nanoparticles in step (1) is 200-250 grams.
[0020] Furthermore, in the step (6), urea, formaldehyde and deionized water are mixed and the pH value of the solution is adjusted to 9, the mixed solution is heated in a water bath at 50 to 70° C., and the mixed solution is cooled to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 5 to 7 grams and the amount of formaldehyde added is 4 to 6 grams per 100 milliliters of deionized water.
[0021] Furthermore, the curing agent in step (7) is aromatic acid anhydride, and the pH regulator is disodium hydrogen phosphate.
[0022] Furthermore, in step (7), the water bath reaction temperature is 50-70° C., and the water bath reaction time is 4-6 hours.
[0023] The present invention discloses a method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media. Compared with the existing technology, the method has the following beneficial effects: in order to solve the problem that it is difficult to strike a balance between high self-repair performance and low doping amount of self-repair components in composite media, the method of the present invention utilizes γ-Al2O3@SiO2 nanoparticles to replace traditional ionic emulsifiers, and at the same time enables the produced microcapsules to have magnetically controlled properties, and can use a magnetic field to guide the directional migration of a small amount of microcapsules when synthesizing composite materials, thereby realizing efficient self-repair of the composite material at a low capsule doping amount, and effectively solving the problem that it is difficult to strike a balance between high self-repair performance and low doping amount of self-repair components in composite media.
[0024] The invention discloses a method for preparing magnetically controlled microcapsules for self-repairing electrical tree damage of insulating media. The method comprises the following steps: acidifying γ-Al2O3 nanoparticles, placing the γ-Al2O3 nanoparticles in a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water for ultrasonic modification, adding tetraethyl orthosilicate, and performing multiple modifications, so that the γ-Al2O3@SiO2 nanoparticles obtained by the reaction are highly magnetic and have a higher yield, which makes it easier to guide a small amount of microcapsules to migrate in a directional manner under the guidance of a magnetic field, and reduces the production cost. The prepared magnetically controlled microcapsules have good repairing effect, and an addition amount of 5wt% of the magnetically controlled microcapsules can effectively repair electrical tree damage, reducing the average electrical tree length before repair to less than 300μm, and maintaining the breakdown strength of the repaired sample at more than 95% of that of the epoxy resin substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the preparation process of the magnetically controlled microcapsules of the present invention. DETAILED DESCRIPTION
[0026] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0027] Example 1
[0028] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0029] (1) 5 g of γ-Al2O3 nanoparticles were subjected to an acid treatment, wherein the acid treatment solution used for the acid treatment consisted of sulfuric acid and hydrogen peroxide, and the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment solution was: sulfuric acid: hydrogen peroxide = 6.5:3; the acid treatment temperature was 75° C., the acid treatment time was 50 min, and solid-liquid separation was performed to obtain acidified γ-Al2O3 nanoparticles; the amount of the acid treatment solution used was 1 L;
[0030] The acidified γ-Al2O3 nanoparticles are added to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water and ultrasonically treated for 50 minutes to obtain a modified mixed solution of γ-Al2O3 nanoparticles; the volume ratio of the anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100:23:1.8; the concentrated ammonia water is an aqueous solution containing 25% ammonia; the amount of the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is 300 ml;
[0031] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles, ultrasonically treating the mixture for 25 min, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 14 ml;
[0032] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 5:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0033] (4) adding 4 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 68° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0034] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:8:4:0.08; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 200 grams;
[0035] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 50° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 5 g and the amount of formaldehyde added is 4 g per 100 ml of deionized water;
[0036] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the mixture is reacted in a water bath at 50° C. for 4 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0037] The magnetically controlled microcapsules prepared in this embodiment were tested, and the test results are shown in Table 1 below;
[0038] Table 1
[0039]
[0040]
[0041] Example 2
[0042] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0043] (1) 5 g of γ-Al2O3 nanoparticles were subjected to an acid treatment, wherein the acid treatment solution used for the acid treatment consisted of sulfuric acid and hydrogen peroxide, and the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment solution was: sulfuric acid: hydrogen peroxide = 7.5:3; the acid treatment temperature was 85°C, the acid treatment time was 70 min, and solid-liquid separation was performed to obtain acidified γ-Al2O3 nanoparticles; the amount of the acid treatment solution used was 1 L;
[0044] The acidified γ-Al2O3 nanoparticles are added to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water and ultrasonically treated for 70 minutes to obtain a modified mixed solution of γ-Al2O3 nanoparticles; the volume ratio of the anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100:27:2.2; the concentrated ammonia water is an aqueous solution containing 28% ammonia; the amount of the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is 300 ml;
[0045] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treating the mixture for 35 min, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 16 ml;
[0046] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 8:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0047] (4) adding 7.5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 72° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0048] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:12:6:0.12; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 250 grams;
[0049] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 70° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 7 g and the amount of formaldehyde added is 6 g per 100 ml of deionized water;
[0050] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 70° C. for 6 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0051] The magnetically controlled microcapsules prepared in this embodiment were tested, and the test results are shown in Table 2 below;
[0052] Table 2
[0053]
[0054] Example 3
[0055] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0056] (1) 5 g of γ-Al2O3 nanoparticles were subjected to an acid treatment, wherein the acid treatment solution used for the acid treatment consisted of sulfuric acid and hydrogen peroxide, wherein the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment solution was: sulfuric acid: hydrogen peroxide = 7:3; the acid treatment temperature was 80° C., the acid treatment time was 60 min, and solid-liquid separation was performed to obtain acidified γ-Al2O3 nanoparticles; the amount of the acid treatment solution used was 1 L;
[0057] The acidified γ-Al2O3 nanoparticles are added to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water and ultrasonically treated for 60 minutes to obtain a modified mixed solution of γ-Al2O3 nanoparticles; the volume ratio of anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100:25:2; the concentrated ammonia water is an aqueous solution containing 26% ammonia; the amount of the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is 300 ml;
[0058] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treating the mixture for 30 minutes, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 15 ml;
[0059] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 6:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0060] (4) adding 5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 70° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0061] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:10:5:0.1; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 220 grams;
[0062] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 60° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6 g and the amount of formaldehyde added is 5 g per 100 ml of deionized water;
[0063] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 60° C. for 5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0064] The magnetically controlled microcapsules prepared in this embodiment were tested, and the test results are shown in Table 3 below;
[0065] Table 3
[0066]
[0067]
[0068] Example 4
[0069] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0070] (1) 5 g of γ-Al2O3 nanoparticles were subjected to an acid treatment, wherein the acid treatment solution used for the acid treatment consisted of sulfuric acid and hydrogen peroxide, and the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment solution was: sulfuric acid: hydrogen peroxide = 6.8:3; the acid treatment temperature was 78° C., the acid treatment time was 65 min, and solid-liquid separation was performed to obtain acidified γ-Al2O3 nanoparticles; the amount of the acid treatment solution used was 1 L;
[0071] The acidified γ-Al2O3 nanoparticles are added to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water and ultrasonically treated for 55 minutes to obtain a modified mixed solution of γ-Al2O3 nanoparticles; the volume ratio of anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100:26:2.1; the concentrated ammonia water is an aqueous solution containing 27% ammonia; the amount of the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is 300 ml;
[0072] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treating the mixture for 28 minutes, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 15.5 ml;
[0073] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 7.5:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0074] (4) adding 5.5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 69° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0075] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:9:5:0.09; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 240 grams;
[0076] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 58° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6.5 g and the amount of formaldehyde added is 5.5 g per 100 ml of deionized water;
[0077] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 58° C. for 5.5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0078] The magnetically controlled microcapsules prepared in this example were tested, and the test results are shown in Table 4 below;
[0079] Table 4
[0080]
[0081] Comparative Example 1
[0082] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0083] (1) 5 g of γ-Al2O3 nanoparticles are added to a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water and subjected to ultrasonic treatment for 60 min to obtain a γ-Al2O3 nanoparticle modified mixed solution; the volume ratio of anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100:25:2; the concentrated ammonia water is an aqueous solution containing 26% ammonia; the amount of the mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water is 300 ml;
[0084] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treating the mixture for 30 minutes, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 15 ml;
[0085] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 6:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0086] (4) adding 5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 70° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0087] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:10:5:0.1; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 220 grams;
[0088] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 60° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6 g and the amount of formaldehyde added is 5 g per 100 ml of deionized water;
[0089] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 60° C. for 5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0090] The magnetically controlled microcapsules prepared in this example were tested, and the test results are shown in Table 5 below;
[0091] Table 5
[0092]
[0093] Comparative Example 2
[0094] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0095] (1) 5 g of γ-Al2O3 nanoparticles were subjected to an acid treatment, wherein the acid treatment solution used for the acid treatment consisted of sulfuric acid and hydrogen peroxide, wherein the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment solution was: sulfuric acid: hydrogen peroxide = 7:3; the acid treatment temperature was 80° C., the acid treatment time was 60 min, and solid-liquid separation was performed to obtain acidified γ-Al2O3 nanoparticles; the amount of the acid treatment solution used was 1 L;
[0096] The acidified γ-Al2O3 nanoparticles were added into 300 ml of deionized water and ultrasonically treated for 60 min to obtain a γ-Al2O3 nanoparticle modified mixed solution;
[0097] (2) adding tetraethyl orthosilicate to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treating the mixture for 30 minutes, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; the amount of tetraethyl orthosilicate added was 15 ml;
[0098] (3) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 6:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0099] (4) adding 5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 70° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0100] (5) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:10:5:0.1; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 220 grams;
[0101] (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 60° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6 g and the amount of formaldehyde added is 5 g per 100 ml of deionized water;
[0102] (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 60° C. for 5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0103] The magnetically controlled microcapsules prepared in this example were tested, and the test results are shown in Table 6 below;
[0104] Table 6
[0105]
[0106]
[0107] Comparative Example 3
[0108] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0109] (1) 5 g of γ-Al2O3 nanoparticles, 15 ml of ethyl orthosilicate, and 300 ml of deionized water were ultrasonically treated for 30 min and solid-liquid separated to obtain γ-Al2O3@SiO2 nanoparticles;
[0110] (2) washing the γ-Al2O3@SiO2 nanoparticles with deionized water, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = 6:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0111] (3) adding 5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 70° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0112] (4) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:10:5:0.1; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 220 grams;
[0113] (5) mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 60° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6 g and the amount of formaldehyde added is 5 g per 100 ml of deionized water;
[0114] (6) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 60° C. for 5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0115] The magnetically controlled microcapsules prepared in this embodiment were tested, and the test results are shown in Table 7 below;
[0116] Table 7
[0117]
[0118] Comparative Example 4
[0119] A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media comprises the following steps:
[0120] (1) 5 g of γ-Al2O3 nanoparticles, 3 g of silicon dioxide, and 300 ml of deionized water were ultrasonically treated for 30 min and solid-liquid separated to obtain γ-Al2O3@SiO2 nanoparticles;
[0121] (2) adding γ-Al2O3@SiO2 nanoparticles into a mixed solution of 300 ml of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solution is: anhydrous ethanol: deionized water = 6:10, to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution;
[0122] (3) adding 5 g of silane coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully at 70° C., washing the product, and vacuum drying the product to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion;
[0123] (4) adding a microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; the microcapsule core material is composed of an epoxy resin, a reactive diluent, a photoinitiator and an infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100:10:5:0.1; the amount of microcapsule core material added per gram of the γ-Al2O3 nanoparticles in step (1) is 220 grams;
[0124] (5) mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath at 60° C., and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 6 g and the amount of formaldehyde added is 5 g per 100 ml of deionized water;
[0125] (6) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; aromatic anhydride is further added to the Pickering emulsion as a curing agent, disodium hydrogen phosphate is added as a pH regulator, and the reaction is carried out in a water bath at 60° C. for 5 hours. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
[0126] The magnetically controlled microcapsules prepared in this example were tested, and the test results are shown in Table 8 below;
[0127] Table 8
[0128]
[0129] The magnetically controlled microcapsules prepared in the above Examples 1-4 can make the microcapsules migrate in a directional manner under the guidance of the magnetic field; the magnetically controlled microcapsules prepared in the above Comparative Examples 1-4 cannot make the microcapsules migrate in a directional manner under the guidance of the magnetic field. It can be seen that the magnetically controlled microcapsules prepared by the method of the present invention can make the directional migration of microcapsules guided by the magnetic field easier, have stronger operability, can be applied to more scenarios, and have higher practicality.
[0130] It can be seen that the present invention is a method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage of insulating media. Aiming at the problem that it is difficult to take both high self-repair performance and low doping amount of self-repair components into consideration in composite media, the present invention utilizes γ-Al2O3@SiO2 nanoparticles to replace traditional ionic emulsifiers, and at the same time enables the produced microcapsules to have magnetically controlled properties. When synthesizing composite materials, a magnetic field can be used to guide the directional migration of a small amount of microcapsules, thereby achieving efficient self-repair of composite materials at low capsule doping amounts, effectively solving the problem that it is difficult to take both high self-repair performance and low doping amount of self-repair components of composite media into consideration; the γ-Al2O3 nanoparticles are acidified, and then γ-Al2O3 nanoparticles are ultrasonically modified in a mixed solution of anhydrous ethanol, deionized water and concentrated ammonia water, and then tetraethyl orthosilicate is added. After multiple modifications, the γ-Al2O3@SiO2 nanoparticles obtained by the reaction are magnetic and have a higher yield. On the one hand, it makes it easier to guide the directional migration of a small number of microcapsules under the guidance of the magnetic field, and on the other hand, it reduces the production cost. The prepared magnetically controlled microcapsules have a good repair effect. The addition of 5wt% of the magnetically controlled microcapsules can effectively repair electrical tree damage, reducing the average electrical tree length before repair to less than 300μm, and the breakdown strength of the repaired sample is maintained at more than 95% of the epoxy resin substrate.
[0131] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media, characterized in that: The following steps are involved: (1) acidifying the γ-Al2O3 nanoparticles, and then adding the acidified γ-Al2O3 nanoparticles into a mixed solution consisting of anhydrous ethanol, deionized water and concentrated ammonia water for ultrasonic treatment to obtain a γ-Al2O3 nanoparticle modified mixed solution; (2) adding tetraethyl orthosilicate to the γ-Al2O3 nanoparticle modified mixed solution to fully react, and magnetically separating the product to obtain γ-Al2O3@SiO2 nanoparticles; (3) washing the γ-Al2O3@SiO2 nanoparticles, vacuum drying, and then adding the dried γ-Al2O3@SiO2 nanoparticles into a mixed solution of anhydrous ethanol and deionized water to obtain a γ-Al2O3@SiO2 nanoparticle mixed solution; (4) adding a coupling agent to the γ-Al2O3@SiO2 nanoparticle mixture to react fully, washing the product, and vacuum drying it to obtain treated γ-Al2O3@SiO2 nanoparticles; mixing the treated γ-Al2O3@SiO2 nanoparticles with deionized water to obtain a nanoparticle aqueous dispersion; (5) adding the microcapsule core material to the nanoparticle aqueous dispersion for emulsification to obtain a Pickering emulsion; (6) Mixing urea, formaldehyde and deionized water and adjusting the pH value of the solution to 9, heating the mixed solution in a water bath, and cooling the mixed solution to room temperature to obtain a urea-formaldehyde resin prepolymer solution; (7) The pH value of the urea-formaldehyde resin prepolymer solution is adjusted to neutral, and the solution is added to the Pickering emulsion; a curing agent and a pH regulator are continuously added to the Pickering emulsion, and the reaction is carried out in a water bath. The product is filtered, washed, and vacuum dried to obtain the magnetically controlled microcapsules.
2. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: The acid treatment liquid used for acid treatment of the γ-Al2O3 nanoparticles in step (1) is composed of sulfuric acid and hydrogen peroxide, and the volume ratio of sulfuric acid to hydrogen peroxide in the acid treatment liquid is: sulfuric acid: hydrogen peroxide = (6.5-7.5):3; the acid treatment temperature is 75-85°C, and the acid treatment time is 50-70 minutes; each liter of the acid treatment liquid can treat 4-6 grams of the γ-Al2O3 nanoparticles.
3. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: In the step (1), the volume ratio of anhydrous ethanol, deionized water and concentrated ammonia water in the mixed solution composed of anhydrous ethanol, deionized water and concentrated ammonia water is: anhydrous ethanol: deionized water: concentrated ammonia water = 100: (23-27): (1.8-2.2); the concentrated ammonia water is an aqueous solution containing 25% to 28% ammonia; and the ultrasonic treatment time is 50 to 70 minutes.
4. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: In the step (2), tetraethyl orthosilicate is added to the modified mixed solution of the γ-Al2O3 nanoparticles and ultrasonically treated for 25 to 35 minutes, and the product is magnetically separated to obtain γ-Al2O3@SiO2 nanoparticles; wherein the amount of tetraethyl orthosilicate added per gram of the γ-Al2O3 nanoparticles in step (1) is 2.8 to 3.2 milliliters.
5. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: In the step (3), the volume ratio of anhydrous ethanol to deionized water in the mixed solution of anhydrous ethanol and deionized water is: anhydrous ethanol: deionized water = (5-8):
10.
6. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: The coupling agent in step (4) is a silane coupling agent, and the reaction temperature is between 68° C. and 72° C., wherein the amount of the silane coupling agent added is 80% to 150% of the weight of the γ-Al2O3 nanoparticles in step (1).
7. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: The microcapsule core material in step (5) is composed of epoxy resin, reactive diluent, photoinitiator and infrared fluorescent agent, and the weight ratio of each component is: epoxy resin: reactive diluent: photoinitiator: infrared fluorescent agent = 100: (8-12): (4-6): (0.08-0.12); the addition amount of the microcapsule core material corresponding to each gram of the γ-Al2O3 nanoparticles in step (1) is 200-250 grams.
8. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: In the step (6), urea, formaldehyde and deionized water are mixed and the pH value of the solution is adjusted to 9, the mixed solution is heated in a water bath at 50 to 70° C., and the mixed solution is cooled to room temperature to obtain a urea-formaldehyde resin prepolymer solution; wherein the amount of urea added is 5 to 7 grams and the amount of formaldehyde added is 4 to 6 grams per 100 ml of deionized water.
9. The method for preparing a magnetically controlled microcapsule for self-repair of electrical tree damage in insulating medium according to claim 1, characterized in that: The curing agent in step (7) is aromatic acid anhydride, and the pH regulator is disodium hydrogen phosphate.
10. The method for preparing magnetically controlled microcapsules for self-repair of electrical tree damage in insulating media according to claim 1, characterized in that: In step (7), the water bath reaction temperature is 50-70° C., and the water bath reaction time is 4-6 hours.